A Developmental Examination of Narrative Writing in EL and EL1 School Children Who Are Typical Readers, Poor Decoders, or Poor Comprehenders. (January 2020) - Herbert, Katherine E. D.; Massey-Garrison, Angela; Geva, Esther
This longitudinal study examined story-writing development of students from Grade 4 to Grade 6, comparing the developmental trajectories of English as a first language (EL1s; n = 43) and English learners (ELs; n = 108) in general, and in groups of EL1s and ELs with typically developing and poor reader profiles. In relation to their EL1 or EL reference group, students were classified in Grade 4 as typical readers ( n = 72), poor decoders ( n = 53), or poor comprehenders ( n = 26), with EL1s and ELs proportionally represented in each group. The effects of language, grade level, and reading group on story-writing measures were examined. Both EL1s and ELs developed story-writing skills in a similar manner, showing significant growth between Grades 4 and 6. Typically developing ELs attained age-appropriate story-writing levels. Poor decoders and poor comprehenders showed similar profiles of strengths and weaknesses, regardless of whether English was their first or second language. Both poor reader groups had significant difficulties in story-writing, struggling with the mechanics of writing, sentence structure, and story organization. Findings are discussed in terms of the interconnected relationship between reading and writing profiles, and the importance of a comprehensive understanding of sources of learning difficulties in ELs and EL1s.